2023
DOI: 10.1101/2023.06.27.546786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methylphenidate alleviates cognitive dysfunction from early Mn exposure: Role of catecholaminergic receptors

Abstract: BACKGROUND: Environmental manganese (Mn) exposure is associated with impair-ments in attention and psychomotor function as well as impulsivity/hyperactivity in children and adolescents. We have shown previously that developmental Mn exposure can cause these same areas of dysfunction in a rat model. Although treatment with methylphenidate (MPH) is well documented to lessen impairments in attention, im-pulse control, and sensorimotor function in children, it is unknown whether this treat-ment is effective in imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…The catecholaminergic system in the prefrontal cortex/anterior cingulate cortex has been well-established as critical to executive functioning, including attention, emotion regulation, error monitoring, and behavioral inhibition [107][108][109][110][111][112][113] , and thus Mn-induced alterations to this system may well underlie the ADHD-like behavioral phenotype of the Mn exposed animals. This inference is further supported by studies from our group showing that oral methylphenidate (a catecholamine reuptake inhibitor) ameliorates the Mn behavioral deficits in attention and sensorimotor function 19,21,114 . Notably, our group has also demonstrated that developmental Mn exposure causes lasting alterations in DNA methylation and expression of genes related to DNA methylation, neuronal development and catecholaminergic neuronal systems in our rat model 115 , and other studies have also shown that Mn exposure can lead to altered DNA methylation [116][117][118][119] .…”
Section: Putative Neurobiological Mechanismsmentioning
confidence: 65%
“…The catecholaminergic system in the prefrontal cortex/anterior cingulate cortex has been well-established as critical to executive functioning, including attention, emotion regulation, error monitoring, and behavioral inhibition [107][108][109][110][111][112][113] , and thus Mn-induced alterations to this system may well underlie the ADHD-like behavioral phenotype of the Mn exposed animals. This inference is further supported by studies from our group showing that oral methylphenidate (a catecholamine reuptake inhibitor) ameliorates the Mn behavioral deficits in attention and sensorimotor function 19,21,114 . Notably, our group has also demonstrated that developmental Mn exposure causes lasting alterations in DNA methylation and expression of genes related to DNA methylation, neuronal development and catecholaminergic neuronal systems in our rat model 115 , and other studies have also shown that Mn exposure can lead to altered DNA methylation [116][117][118][119] .…”
Section: Putative Neurobiological Mechanismsmentioning
confidence: 65%